An Online Physical Activity Intervention for Youth With Physical Disabilities: A Pilot Study - Sharma, Ritu; Latimer-Cheung, Amy E.; Cairney, John; Arbour-Nicitopoulos, Kelly P. (Frontiers in Rehabilitation Sciences, 2021)
Background: Physical activity (PA) interventions are limited in number and reach for youth with physical disabilities (YPD) who experience systemic barriers that may preclude their in-person participation. Further, a lack of theory in the development and evaluation of PA interventions impedes our understanding and replication of active components of behavior change. These limitations pose challenges in the effective promotion of PA in YPD. Theory-based and more inclusive methods of PA intervention delivery must be explored in our efforts to promote PA and overall health in YPD. Methods: A pilot study was conducted to evaluate the feasibility and outcomes of an online, four-week social cognitive theory-based PA intervention for YPD. Intervention feasibility (implementation fidelity, intervention compliance, and intervention acceptability) was evaluated through manual documentation, weekly feedback questionnaires, and open-ended feedback at one-month post-intervention. Targeted social cognitive (outcome expectations, self-efficacy [task, barrier, self-regulatory] and self-regulation) and PA behavior outcomes were self-reported at baseline and one-week and one-month post-intervention. Results: Sixteen YPD (Mage = 17.4 ± 2.7 years, 69% female) completed the study. Intervention feasibility was supported by high implementation fidelity (100%), high intervention compliance (>90%), and positive ratings on indicators of acceptability for all weeks of the intervention (weekly feedback questionnaire means ranging from 5.74 to 6.19 out of 7). Through open-ended feedback, participants indicated the intervention was easy to use and understand, favourably shifted their self-awareness and personal meaning of PA, and provided value and potential for future use pertaining to the learned self-regulation skills and strategies. Participants also provided formatting and content recommendations for intervention improvement. Repeated measures ANOVAs showed significant and large effect sizes for changes in participants’ task (p = 01, n2p = .28) and barrier (p = .02, n2p = .24) self-efficacy, goal-setting and planning/scheduling behaviors (ps < .001, n2ps = .42), and self-reported PA behavior (p = .02, n2p = .26). Conclusions: An online PA intervention for YPD is feasible and may offer potential benefit through the enhancement of self-efficacy, self-regulation, and PA behavior. Continued research is necessary to understand the efficacy and longer-term outcomes of online, theory-based interventions for YPD as a PA promotion strategy.